APPLICATION OF SEISMIC DATA PROCESSING FOR SEABED IMAGING - Henry M. Manik; Susilo Hadi (National Institute of Aeronautics and Space of Indonesia (LAPAN), 2010)
The research was conducted in April-May 2010 in North Maluku watersbelonging to the District Luwuk Banggai, Central Sulawesi Province. This area is located atcoordinates 2 ° S - 4 ° S and 123 ° E - 126 ° east. Data processing was done at OceanAcoustics Laboratory, Department of Marine Science and Technology, Bogor AgriculturalUniversity and Marine Geological Institute (MGI) in Bandung. Seismic data processingusing the data in SEG-Y format. The data was computed with Seisee software and bandpass filtering using Matlab. Based on the results of research, it is evident that increasing thefrequency band was followed by the higher the resolution. Sampling point 30 in the form ofsandy clay sediments has an impedance value of 2.49 and the value of reflection coefficientof 0.23. While the sampling point 31 in the form of silty clay in the study showed the valueof the impedance of 1,93 with the reflection coefficient of 0.11.